PENERAPAN TRAUMA HEALING UNTUK MENGATASI KECEMASAN PADA ANAK PASCA BENCANA GEMPA BUMI DI SEKOLAH DASAR NEGEERI MEKARJAYA CIANJUR - Abdur Rahim; Imas Nurjamillah; Ima Hafidah; M. Nur Fauzy; Zahra Putri Alhaqni (LPPM Universitas Bina Bangsa, 2023)
Community service carried out by students does not mean teaching the community about what is best for them, but carrying out empowerment as a process of searching (research) carried out together to find the best way to solve the problems they face. The purpose of community service activities in the form of trauma healing carried out on children is to reduce anxiety levels and restore children's emotional condition after the disaster, so that they can help the spirit return to how it was before the disaster occurred with various kinds of games played both individually and groups as well as the provision of material that aims to improve the characteristics of the child. The implementation of trauma healing uses the Participatory Rapid Appraisal (PRA) method or participatory village assessment which is carried out through various activities such as observation, surveys, and interviews